Comparing Multi-Arm Robotics for In-Space Assembly - McBryan, Katherine (Frontiers in Space Technologies, 2022)
Robotic In-space assembly (ISA) is the next step to building larger and more permanent structures in orbit. Determining the best robot for ISA is difficult as it will not only depend on the structure being assembled but on how it is assembled. This analysis shows how changing some key design parameters can influence different robotic systems for ISA. This study focuses on the construction of a 20m linear truss structure. Two categories of robots are included in this study: a stationary robot and a mobile robot which crawls along the structure. Both the stationary and crawling robotic systems utilize two planar dexterous manipulators to assemble individual truss pieces into a linear truss. In the case of the stationary robotic system a single long positioning leg is used to move the two dexterous arms into position. The crawling robotic system uses two planar manipulators to crawl along the truss. A systems level analysis is presented which details how the forces from the robotic systems drive the mass of the truss and also how the size of the truss segments drive the requirements of the robotic system. This analysis shows how changing some key design parameters can influence each of the different robotic systems and the truss design itself. The estimated mass of the robotic systems and the truss, the energy, and the assembly time are presented. There are trade-offs to every robot design and understanding those trade-offs is essential to building a system that is not only efficient but also cost-effective.